2016
DOI: 10.1177/1049731516656802
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of the Transracial Adoption Parenting Scale—Revised

Abstract: The purpose of this research is to provide an initial validation of a revision of the Transracial Adoption Parenting Scale-Revised (TAPS-R) with international transracial adoptive parents. Method: This study employed a cross-sectional, online survey design to recruit transracial adoptive parents from a parent support group, Families for Chinese Children. Results: Exploratory factor analysis reveals that the 47-item TAPS-R is a valid scale, which includes four factors: racial awareness, multicultural planning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In a similar vein, two measures of familial ethnic–racial socialization specific to the context of transracial adoption emerged. One measure (Langrehr, Thomas, & Morgan, ) focused on prejudice awareness, racial–ethnic pride, and egalitarianism, whereas the second (J. Lee, Crolley‐Simic, & Vonk, ) focused on racial awareness, multicultural planning, integration, and coping skills. We also saw increased attention to earlier developmental periods, as Derlan et al () published two measures targeting caregivers' (a) attitudes about the importance of engaging in ethnic–racial socialization with their children about race and ethnicity and (b) ethnic–racial socialization behaviors.…”
Section: Methodological Advances and Insightsmentioning
confidence: 99%
“…In a similar vein, two measures of familial ethnic–racial socialization specific to the context of transracial adoption emerged. One measure (Langrehr, Thomas, & Morgan, ) focused on prejudice awareness, racial–ethnic pride, and egalitarianism, whereas the second (J. Lee, Crolley‐Simic, & Vonk, ) focused on racial awareness, multicultural planning, integration, and coping skills. We also saw increased attention to earlier developmental periods, as Derlan et al () published two measures targeting caregivers' (a) attitudes about the importance of engaging in ethnic–racial socialization with their children about race and ethnicity and (b) ethnic–racial socialization behaviors.…”
Section: Methodological Advances and Insightsmentioning
confidence: 99%
“…Although they hope that knowing the language gives their children more opportunities to engage with people from their birth culture, the adoptive parents recognize that this might not be enough to integrate their children into these spaces (Breshears, 2022). Survival skills, later called coping skills (J. Lee et al, 2018), refer to transracial adoptive parents’ recognition of the need to prepare their children to cope with racism and the ability to impart the necessary skills to do so (Vonk, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on parental perception of their socialization practices is a limitation as one study showed that parents tended to report engaging in higher levels of socialization practices than their children reported (Hu, Zhou, & Lee, 2017). In an age of colorblindness, defined as "the denial of racial dynamics," many white parents are unequipped to address the multifaceted ways in which racism, bias, and discrimination affect people of color in society, even (or especially) when it comes to their TRA (Lee, Crolley-Simic & Vonk, 2018;Morgan & Langrehr, 2019). In same race families of color, discussion of racial structures in society is a common practice in many homes and built within the family structure (Morgan & Langrehr, 2019).…”
Section: Developing Racial-ethnic Identitymentioning
confidence: 99%
“…The development of a racial or ethnic identity comes about through racial awareness, cultural socialization, and racial socialization (Lee, Crolley-Simic & Vonk, 2018). Racial awareness is one's understanding of race in their own life and in other people's lives.…”
Section: Developing Racial-ethnic Identitymentioning
confidence: 99%
See 1 more Smart Citation